Bioengineering Comamonas testosteroni CNB-1: a robust whole-cell biocatalyst for efficient PET microplastic degradation - Zhanqing Cao; Wei Xia; Shilei Wu; Jiale Ma; Xiaoli Zhou; Xiujuan Qian; Anming Xu; Weiliang Dong; Min Jiang (Bioresources and Bioprocessing, 2023)
Abstract The escalating crisis of polyethylene terephthalate (PET) microplastic contamination in biological wastewater treatment systems is a pressing environmental concern. These microplastics inevitably accumulate in sewage sludge due to the absence of effective removal technologies. Addressing this urgent issue, this study introduces a novel approach using DuraPETase, a potent enzyme with enhanced PET hydrolytic activity at ambient temperatures. Remarkably, this enzyme was successfully secreted from Comamonas testosteroni CNB-1, a dominant species in the active sludge. The secreted DuraPETase showed significant hydrolytic activity toward p-NPB and PET nanoplastics. Furthermore, the CNB-1 derived whole-cell biocatalyst was able to depolymerize PET microplastics under ambient temperature, achieving a degradation efficiency of 9% within 7 days. The CNB-1-based whole biocatalysts were also capable of utilizing PET degradation intermediates, such as terephthalic acid (TPA) and ethylene glycol (EG), and bis(2-hydroxyethyl)-TPA (BHET), for growth. This indicates that it can completely mineralize PET, as opposed to merely breaking it down into smaller molecules. This research highlights the potential of activated sludge as a potent source for insitu microplastic removal. Graphical Abstract